Hisbah in the Context of Shariah Governance in Islamic Finance: A Comparison Between Indonesia and Malaysia - Febrina, Ilza; Abdulah, Budiman (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The Role of Hisbah has been more essential in contemporary world in promoting Ethical Values and Justice in the Society. In Islamic finance setting, the role of Hisbah has been increasingly relevant in modern financial governance especially to ensure that its operation align with the ethical standards and Shariah principles. This paper is aimed to overview the concept and urgency of Hisbah and several related major issues such as Core values of the Shariah governance framework (SGF) in Islamic Finance, at last to further discuss the SGF’s comparison between Malaysia and Indonesia. The paper adopts a descriptive approach to examine the role of Hisbah in Islamic Finance specifically in the context of SGF. The data, sourced from various journals and books were collected and analysed to find the conclusion regarding the role of Hisbah in promoting adherence to Sharia principles in contemporary Islamic Finance and a brief comparative overview of SGF between Malaysia and Indonesia. The findings of the paper highlight that Malaysia's Shariah governance framework is characterized by a centralized, standardized approach with compliance mechanisms strictly enforced through BNM and SAC to ensure consistency. In contrast, the Indonesian framework is more flexible. the DSN-MUI gives guidance for IFIs as an independent body that exercise their discretion in interpreting Shariah rulings. These two approaches represent the level of regulatory priorities and development aspects of Islamic finance in each country.